An assessment of location data requirements in logistics. (1st January 2013) - Musa, Ahmed; Gunasekaran, Angappa; Yusuf, Yahaya; Azua, Samuel; Terwase, Youngu
In the geolocation and navigation community, requirements for location data are often expressed in terms of accuracy, integrity and availability of location information in both time and space. The question arises as to what these requirements are across the application spectrum in logistics and the technologies available to meet the needs. The answer to this question is not as straightforward as it might first seem, given the diversity of potential applications and the plethora of technologies currently available, or are being developed, to meet various industrial needs. Based on a specially-designed Delphi study with experts across industries, this paper provides some specific information and guidance in this regard. The results presented in this paper can be used by the logistics, geolocation and semiconductor industries alike in identifying the geolocation needs of their various applications and how those needs can be fulfilled.